Endoscopy-assisted anterior cervical discectomy and fusion with internal fixation vs conventional surgery in the treatment of cervical disc herniation - Haicun Zhang; Yanbo Lin; Canglu Wu; Fangling Cheng; Danqing Bao; Yuyan Chen (Videosurgery and Other Miniinvasive Techniques)
Introduction: Cervical disc herniation (CDH) is a common condition, usually caused by excessive strain or trauma to the spine. Initially, it is treated conservatively; however, complex and resistant cases may require a surgical intervention.